2022
DOI: 10.1002/aic.17919
|View full text |Cite
|
Sign up to set email alerts
|

Mixed oxygen ionic‐carbonate ionic conductor membrane reactor for coupling CO2 capture with in situ methanation

Abstract: CO 2 methanation is one of the vital reactions to utilize CO 2 and realize power to gas process. To decrease the CO 2 capture cost and alleviate the hot spots during the strong exothermic methanation reaction, here, we report a coupling of CO 2 capture process with in situ CO 2 methanation process through a ceramic-molten carbonate (MC) dual phase membrane reactor over the Ni-based catalyst. The performance of the membrane reactor was systematically investigated and compared with the traditional fixed-bed reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The results reveal that the CO 2 permeation flux in the membrane reactor with a 10% H 2 /He gas sweep is approximately four times higher (1.04 versus 4.25 mL•cm −2 •min −1 ) than that of a single CO 2 separation process utilizing pure He sweeping. Zhu et al [84] reported an SDC-carbonate dual-phase membrane reactor coupling of CO 2 separation with CO 2 methanation reaction over a Ni-based catalyst. In general, the carbonate dual-phase membrane reactors based on the first mode (refer to Figure 12a) primarily emphasize enhancing CO 2 capture through its coupling with the CO 2 reforming reaction.…”
Section: Membrane Reactor Conceptmentioning
confidence: 99%
“…The results reveal that the CO 2 permeation flux in the membrane reactor with a 10% H 2 /He gas sweep is approximately four times higher (1.04 versus 4.25 mL•cm −2 •min −1 ) than that of a single CO 2 separation process utilizing pure He sweeping. Zhu et al [84] reported an SDC-carbonate dual-phase membrane reactor coupling of CO 2 separation with CO 2 methanation reaction over a Ni-based catalyst. In general, the carbonate dual-phase membrane reactors based on the first mode (refer to Figure 12a) primarily emphasize enhancing CO 2 capture through its coupling with the CO 2 reforming reaction.…”
Section: Membrane Reactor Conceptmentioning
confidence: 99%
“…This is in accordance with the general tendency of gas absorption in a liquid. 72 Because the solubility in [N 1111 ][Eaca] exceeds 0.5 mol of CO 2 per mole of the IL, it is reasonable to infer that both the equimolar and 2:1 mechanisms are responsible for the high absorption of CO 2 , as shown in Equations (7) and (8).…”
Section: Thermodynamic Modeling and Analysis Of Absorption Mechanismmentioning
confidence: 99%
“…In the past two decades, CO 2 capture using ionic liquids (ILs) has attracted much attention, and has been recognized as a very promising technology. [5][6][7][8] New methods have been developed to capture CO 2 efficiently using ILs through chemical interactions. [9][10][11] ILs have their own unique properties that favor for practical applications.…”
Section: Introductionmentioning
confidence: 99%